Ekranisasi Novel Ke Dalam Film “Eminus Dolere: Panduan Mempersiapkan Perpisahan” Karya Arman Dhani (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research aims to describe the process of translating a novel into the film "Eminus Dolere: A Guide to Preparing for Farewell by Arman Dhani." This research is a type of research that uses qualitative descriptive methods. This research obtained results in the form of: 1. The Process of Excrementing the Novel Plot into the film Eminus Dolere: A Guide to Preparing Farewell by Arman Dhani for the reduction aspect category of 23 plots. For the aspect category, 12 additional lines were added. For the change category there are 10 variations. 2. The process of ecranizing novel characters into the film Eminus Dolere: A Guide to Preparing Farewell, Arman Dhani's work for the category of shrinking aspects does not experience the elimination of characters. For the additional category, there are 8 figures. For the variation change category there are 8 figures. The process of ecranizing the novel's setting into the film Eminus Dolere: A Guide to Preparing Farewell by Arman Dhani for the background reduction aspect category is 12. For the additional aspect category there are 8 settings. For the change category there are 5 variations in background.